Pre-pyloric Enteral Nutrition versus Total Parenteral Nutrition on Survival in Dogs with Acute Pancreatitis - Ting, Felix Tsz Fung (Veterinary Evidence, 2025)
Question In dogs with acute pancreatitis, does pre-pyloric enteral nutrition compared to total parenteral nutrition result in an improved survival rate? Clinical bottom line Category of research: Treatment. Number and type of study designs reviewed: One paper was critically reviewed. It was an open-label, prospective pilot study. Strength of evidence: Weak. Outcomes reported: There was no difference in outcome between the two treatments in this study. Conclusion: There is currently weak evidence on the effect of pre-pyloric enteral nutrition compared to total parenteral nutrition on the survival rate of dogs with acute pancreatitis.